A Review of Critical Factors Impacting the Implementation of E-government in Developing Countries - Mogale, Boitumelo Hlengiwe (Department of Political Studies, 2022)
A key challenge facing developing countries is the high failure rate of electronic government (e-government) programmes. Since its inception, e-government has been implemented globally with the aim that it will enhance the quality-of-service delivery, transform government's internal and external processes and make the public sector more effective and efficient. However, the majority of e-government initiatives have failed to meet their objectives, particularly in developing countries. Therefore, this research considers the factors facilitating and inhibiting the successful implementation of e-government in developing countries. The methodology adopted for the thesis was a qualitative research approach. Secondary data was collected through a literature review of various sources, namely government publications, annual reports compiled by international development agencies and relevant books. To address the research question, I identified literature from journal articles with expertise in information systems such as the Electronic Journal for E-government. The research findings indicate that e-government in developing countries is impacted by various infrastructural, financial, political, socio-economic, organisational and human related aspects. Some of these include the digital divide, resistance to change, limited ICT skills and a lack of robust regulatory frameworks. The study concludes that successful e-government does not solely rest on technology. Instead, developing countries need to understand the impact of the various local contextual factors. These are the fundamental aspects that must be considered during the strategic design of e-government initiatives to ensure they are appropriate for and relevant to local conditions.